Investigation of Sodium Dithionite Residues in the Rock Candies Produced in the Candies Making Plants of Hamadan, Iran - Abdolmotaleb Seidmohammadi; Gorban Asgari; Abbas Lotfi; Javad Fardmal; Ali Heshmati; Amin Pirmoghani (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Rock candy is one of the most widely used sugar products in Iran. The use of chemical additives in food products can be a serious threat to human health and environment if it is not accompanied with sufficient monitoring and management. Regarding this, the present study was conducted with the aim of investigating the amount of sodium dithionite residue in the rock candies produced in the candy making plants of Hamadan, Iran. Methods: This descriptive and analytical study was conducted on the rock candies produced in all the active candy making plants of Hamadan in 2015. The sampling was performed for four months in 20 rock candy producing plants. The concentration of sodium dithionite residue was determined according to the guidelines released by the Institute of Standards and Industrial Research of Iran. Data analysis was performed using SPSS version 16 and Excel 2013 software. Results: According to the results, sodium dithionite was used as an additive in all rock candy making plants investigated in this study. The highest and lowest concentrations of sodium dithionite were 23.85 and 3.2 mg/kg, respectively. Furthermore, the results indicated that in over 37.5% of total sample size, sodium dithionite concentration was higher than the standard value. The mean concentrations of sodium dithionite in the rock candies produced in March, April, May, and June were 9.7±5.84, 9.49±3.7, 9±3.76, and 7.1±2.99 mg/kg, respectively, which were indicative of significant differences between different months in this regard. Conclusion: As the findings of the present study indicated, the rock candies produced in the majority of the investigated plants had a high sodium dithionite concentration, which was due to the use of unsuitable main ingredients. Therefore, more monitoring and training are needed for the workshop operators.